Obesity impairs resistance to Leishmania major infection in C57BL/6 mice. - Martins, Vinicius Dantas (2020)
An association between increased susceptibility to infectious diseases and obesity has been described as a result of impaired immunity in obese individuals. It is not clear whether a similar linkage can be drawn between obesity and parasitic diseases. To evaluate the effect of obesity in the immune response to cutaneous Leishmania major infection, we studied the ability of C57BL/6 mice fed a hypercaloric diet (HSB) to control leishmaniasis. Mice with diet-induced obesity presented thicker lesions with higher parasite burden and a more intense inflammatory infiltrate in the infected ear after infection with L. major. There was no difference between control and obese mice in IFN-gamma or IL-4 production by auricular draining lymph node cells, but obese mice produced higher levels of IgG1 and IL-17. Peritoneal macrophages from obese mice were less efficient to kill L. major when infected in vitro than macrophages from control mice. In vitro stimulation of macrophages with IL-17 decreased their capacity to kill the parasite. Moreover, macrophages from obese mice presented higher arginase activity. To confirm the role of IL-17 in the context of obesity and infection, we studied lesion development in obese IL-17R-/- mice infected with L. major and found no difference in skin lesions and the leukocyte accumulation in the draining lymph node is redcuced in knockout mice compared between obese and lean animals. Our results indicate that diet-induced obesity impairs resistance to L. major in C57BL/6 mice and that IL-17 is involved in lesion development.